1998
DOI: 10.1099/0022-1317-79-6-1479
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic characteristics of fijiviruses based on nucleotide sequences of the oat sterile dwarf virus genome.

Abstract: Sequence determination of full-length cDNA clones of genomic segments 7-10 (S7-S10) of oat sterile dwarf fijivirus (OSDV) revealed that the 5h and 3h ends of the plus strands of these segments had the same conserved terminal sequences, 5h AACGAAAAA and UUUUUUUAGUC 3h. These sequences are similar, but not identical, to the conserved terminal nucleotide sequences of the genomic segments of rice black streaked dwarf fijivirus (RBSDV) and maize rough dwarf fijivirus (MRDV). The coding strands of S7 and S10 each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…This result is supported by the observation that comparable structural proteins are encoded in similar positions on NLRV S7 and S8, respectively. The sequences of the core capsid and major outer capsid proteins encoded by RBSDV S8 and S10 are homologous to the NLRV amino acid sequences [see the accompanying paper by Isogai et al (1998)]. …”
Section: Discussionmentioning
confidence: 99%
“…This result is supported by the observation that comparable structural proteins are encoded in similar positions on NLRV S7 and S8, respectively. The sequences of the core capsid and major outer capsid proteins encoded by RBSDV S8 and S10 are homologous to the NLRV amino acid sequences [see the accompanying paper by Isogai et al (1998)]. …”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that one or both lysines in motif A are essential for the triphosphatase activities of 2 (18) (see below). Although previous authors have noted similarities to NTP-binding motifs in many of these sequences (8,12,15,18), none have observed that the specific motifs shown in Fig. 1 are conserved among all genera of turreted Reoviridae.…”
mentioning
confidence: 90%
“…In general, different reoviruses infect a wide range of different hosts, including mammals, birds, reptiles, fish, arthropods, fungi, protists, and plants. Reoviruses infecting plant-feeding hemipteran insects are classified into three genera: Phytoreovirus (74,75), Fijivirus (76,77), and Oryzavirus (78). Fijiviruses have 10 linear dsRNA segments encoding 12 proteins (69).…”
mentioning
confidence: 99%